Job Satisfaction of Academic Employees of Camarines Sur Polytechnic Colleges - Astibe, Ma. Eleanor L.; Bermal, Abegail D.; Delatado, Jasmin C.; Marjolino, Antonette B.; Uvero, Mariel N.; Bermal, Marites A. (The Indonesian Institute of Science and Technology Research, 2023)
The study aims to determine the Job Satisfaction of the academic employees of Camarines Sur Polytechnic Colleges. It seeks to determine the profile of the respondents, the level of job satisfaction of academic employees, problems encountered and the significant relationship between the level of job satisfaction of the respondents when grouped according to profile and the recommendations proposed to enhance the level of satisfaction of academic employees. The researchers made use of the descriptive method as the primary gathering tool in the study using percentage technique, rank ordering method and weighted mean formula to compute the profile of the respondents, level of job satisfaction, problems encountered, the significant relationship between the level of job satisfaction of the respondents when grouped according to shape and proposed recommendations. There are 41 regular and contractual service academic employees, and out of 41 respondents, 30 answered the survey questionnaire. Based on the respondent’s profile, the findings are that most respondents are twenty-one to thirty years old, the majority are female, and the majority are instructors. The results showed that academic employees' job satisfaction levels are very satisfied. On the problems encountered by academic employees, the Nature of the job is a slightly severe problem. The significant relationship between the level of job satisfaction, the nature of the job, the work environment and the professional growth of the respondents, when grouped according to profile, has no significant relationship between the levels of job satisfaction. The story of job satisfaction in terms of salaries/benefits by the respondents, when grouped according to profile, position title, and salary grade, has a significant relationship. Regarding job security, the highest educational attainment in salary grade has a meaningful relationship.